VILLAGE WEBSITE DEVELOPMENT TRAINING AS A DIGITAL-BASED SERVICE OPTIMIZATION IN ALANG-ALANG VILLAGE, TRAGAH, BANGKALAN - Setijaningrum, Erna; Ghofiqi, Muhammad; Purwanto, Luqman; Billiyanto, Rendy; Effendy, Faried (Universitas Airlangga, 2025)
The rapid advancement of information technology has significantly impacted the public service sector, including in Alang-Alang Village, Tragah Subdistrict, Bangkalan Regency. Although the Alang-Alang Village Government has developed the Smart Village application, which is used by only around 30% of the population, the village lacks an adequate platform for delivering public service information. To address this issue, a community service initiative was carried out to provide training for village officials in creating and managing a village website. The training involved 25 participants, including the Village Head, village officials, representatives from Tragah Subdistrict, and residents of Alang-Alang Village. The event was held in person at the Alang-Alang Village Office, with the main focus on introducing website features designed to improve transparency, efficiency, and digital-based services. The training covered website management, data privacy, and integration with local policies, facilitated by trainers and mentors from Universitas Airlangga. The effectiveness of the training was assessed using pre- and post-training surveys to measure the participants' improvement in website management skills. Preliminary results indicate that after the launch of the website, there was a noticeable increase in website traffic, with an estimated 40% more residents accessing the platform for public service information. In comparison to the existing Smart Village application, the new website proved to be more user-friendly and accessible to a broader audience, regardless of their device type. To enhance technology adoption, strategies have been implemented to increase awareness and engagement among the community, including follow-up training and continued promotion of the website's benefits.